2022
DOI: 10.3389/fpsyg.2022.768614
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Connectedness in and to Nature: Three Nordic Examples of Recontextualizing Family Therapy to the Outdoors

Abstract: Mentalization-based family therapy and family rehabilitation represent a rich variety of approaches for assisting families with difficult interaction patterns. On the other hand, adventure therapy methods have been successfully used with families to offer them empowering experiences of succeeding together against difficult odds and to improve communication between family members. Further, the health promoting qualities of spending time outdoors are now well established and recognized. The Nordic approach to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Data was collected from urban youth (age group [18][19][20][21][22][23][24][25] residing in the 25 most populated cities in India, exploring their residential exposure to nature through access to green or blue spaces around their residence. The online survey was administered in January 2024.…”
Section: Sample and Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Data was collected from urban youth (age group [18][19][20][21][22][23][24][25] residing in the 25 most populated cities in India, exploring their residential exposure to nature through access to green or blue spaces around their residence. The online survey was administered in January 2024.…”
Section: Sample and Surveymentioning
confidence: 99%
“…Stress reduction interventions, such as Mindfulness-Based Stress Reduction, had greater positive effects on mental health and well-being when conducted outdoors in a natural environment than indoors 22 . Different outdoor activities in nature also help families grow stronger bonds and become closer 23 . Undergraduate students tend to establish identities with themselves, their attitudes, and nature; forming a balanced triadic structure of implicit environmental identity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy was originally aimed at treating borderline personality disorders [ 27 ], but now it is used to treat various types of mental disorders such as depression, eating disorders, drug abuse, and other types of personality disorders [ 11 ]. Mentalization-based therapy (MBT) was initially developed for adults with borderline personality disorder [ 12 ], and subsequent studies by Griffiths et al [ 13 ] and Bo et al [ 14 ] have demonstrated its positive effects on suicidal ideation in adolescents with depression. Mindfulness, widely practiced in Buddhism, can be conceptualized as a specific form of focus [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%